The linkage between functional traits and drone-derived phenology of 74 Northern Hemisphere tree species - Simon Kloos; Marvin Lüpke; Nicole Estrella; Wael Ghada; Jens Kattge; Solveig Franziska Bucher; Allan Buras; Annette Menzel (Science of The Total Environment, 2024)

Maps, trends, and temperature sensitivities—phenological information from and for decreasing numbers of volunteer observers - Ye Yuan; Stefan Härer; Tobias Ottenheym; Gourav Misra; Alissa Lüpke; Nicole Estrella; Annette Menzel (International Journal of Biometeorology, 2021)
Phenology serves as a major indicator of ongoing climate change. Long-term phenological observations are critically important for tracking and communicating these changes. The phenological observation network across Germany is operated by the National Meteorological Service with a major contribution from volunteering activities. However, the number of observers has strongly decreased for the last decades, possibly resulting in increasing uncertainties when extracting reliable phenological information from map interpolation. We studied uncertainties in interpolated maps from decreasing phenological records, by comparing long-term trends based on grid-based interpolated and station-wise observed time series, as well as their correlations with temperature. Interpolated maps in spring were characterized by the largest spatial variabilities across Bavaria, Germany, with respective lowest interpolated uncertainties. Long-term phenological trends for both interpolations and observations exhibited mean advances of −0.2 to −0.3 days year −1 for spring and summer, while late autumn and winter showed a delay of around 0.1 days year −1 . Throughout the year, temperature sensitivities were consistently stronger for interpolated time series than observations. Such a better representation of regional phenology by interpolation was equally supported by satellite-derived phenological indices. Nevertheless, simulation of observer numbers indicated that a decline to less than 40% leads to a strong decrease in interpolation accuracy. To better understand the risk of declining phenological observations and to motivate volunteer observers, a Shiny app is proposed to visualize spatial and temporal phenological patterns across Bavaria and their links to climate change–induced temperature changes.

Does Coltsfoot ( Tussilago farfara L.) have an autumn temperature control to limit precocious flowering in spring? - Tim H. Sparks; Allan Buras; Nicole Estrella; Annette Menzel (International Journal of Climatology, 2020)
The flowering phenology of Coltsfoot ( Tussilago farfara L.) shows a very strong negative response to warmer temperatures in spring (warmer springs = earlier flowering) as reported in numerous studies for other species in Europe and North America. However, despite this, flowering dates in some locations have failed to show a strong advance and, in a small number of cases, have even shown significant delays. Here we use a very extensive data set on first flowering dates (FFD) of Coltsfoot in Germany, firstly on a national scale in the period 1894–2015 and secondly at a regional level in the more thoroughly recorded period from 1951–2015. FFDs were coupled with gridded temperature data using regression techniques to attempt to understand the reasons for the unexpected changes in phenology. National mean FFD did not change significantly over 122 years, although January–March mean temperatures had warmed by 1.2°C. The flowering‐temperature model was significantly improved when the previous September mean temperature was included, which decreased the overall temperature response from 4.5 to 3.7 days/°C. For the more thoroughly recorded period of 1951–2015, January–March mean temperature warmed significantly by 1.7–2.4°C in all 11 German federal state combinations and mean FFD dates advanced by 3–14 days, significant for seven of the States. For 10 of the 11 States, multiple linear regressions explained 79–89% of the observed variation in FFD and evidenced a positive relationship (significant in half of these) with higher temperature in the September preceding flowering (warmer September = later flowering). However, the scale of the September influence is insufficient to explain why Coltsfoot flowering may have stalled or been delayed. The use of controlled experiments to supplement observational data may be necessary to fully understand the drivers of Coltsfoot flowering in spring.

Climate change fingerprints in recent European plant phenology - Annette Menzel; Ye Yuan; Michael Matiu; Tim Sparks; Helfried Scheifinger; Regula Gehrig; Nicole Estrella (Global Change Biology, 2020)
A paper published in Global Change Biology in 2006 revealed that phenological responses in 1971–2000 matched the warming pattern in Europe, but a lack of chilling and adaptation in farming may have reversed these findings. Therefore, for 1951–2018 in a corresponding data set, we determined changes as linear trends and analysed their variation by plant traits/groups, across season and time as well as their attribution to warming following IPCC methodology. Although spring and summer phases in wild plants advanced less (maximum advances in 1978–2007), more (~90%) and more significant (~60%) negative trends were present, being stronger in early spring, at higher elevations, but smaller for nonwoody insect‐pollinated species. These trends were strongly attributable to winter and spring warming. Findings for crop spring phases were similar, but were less pronounced. There were clearer and attributable signs for a delayed senescence in response to winter and spring warming. These changes resulted in a longer growing season, but a constant generative period in wild plants and a shortened one in agricultural crops. Phenology determined by farmers’ decisions differed noticeably from the purely climatic driven phases with smaller percentages of advancing (~75%) trends, but farmers’ spring activities were the only group with reinforced advancement, suggesting adaptation. Trends in farmers’ spring and summer activities were very likely/likely associated with the warming pattern. In contrast, the advance in autumn farming phases was significantly associated with below average summer warming. Thus, under ongoing climate change with decreased chilling the advancing phenology in spring and summer is still attributable to warming; even the farmers’ activities in these seasons mirror, to a lesser extent, the warming. Our findings point to adaptation to climate change in agriculture and reveal diverse implications for terrestrial ecosystems; the strong attribution supports the necessary mediation of warming impacts to the general public.

Climate sensitivity and variation in first flowering of 26 Narcissus cultivars - Anna Bock; Tim H. Sparks; Nicole Estrella; Nigel Jee; Andrew Casebow; Michael Leuchner; Annette Menzel (International Journal of Biometeorology, 2015)

Changes in first flowering dates and flowering duration of 232 plant species on the island of Guernsey - Anna Bock; Tim H. Sparks; Nicole Estrella; Nigel Jee; Andrew Casebow; Christian Schunk; Michael Leuchner; Annette Menzel (Global Change Biology, 2014)
Climate change has affected plant phenology; increasing temperatures are associated with advancing first flowering dates. The impact on flowering duration, however, has rarely been studied. In this study, we analysed first flowering dates and flowering durations from a 27 year dataset of weekly flower observations on 232 plant species from the island of Guernsey in the English Channel. The aim of this study was to explore variation in trends and relationships between first flowering dates, flowering duration and temperature. We specifically looked for evidence that traits, such as life forms and phylogenetic groups, explained variation in sensitivity of first flowering and flowering duration among species. Overall trends revealed significantly earlier flowering over time, by an average of 5.2 days decade −1 since 1985. A highly significant shortening of flowering duration was observed by an average of 10 days decade −1 . Correlations between first flowering, flowering duration and year varied between different species, traits and flowering periods. Significant differences among traits were observed for first flowering and to a lesser degree for flowering duration. Overall, in comparison to first flowering, more species had significant trends in flowering duration. Temperature relationships revealed large differences in strength and direction of response. 55% of the species revealed a significant negative relationship of first flowering dates and temperature. In contrast, only 19% of flowering durations had a significant negative temperature relationship. The advance in first flowering date together with a shortening of flowering duration suggests potentially serious impacts on pollinators, which might pose a major threat to biodiversity, agriculture and horticulture. Human health, in terms of pollen allergies, however, might benefit from a shortening of specific plant pollen seasons.

Erratum to: A comparison of methods to estimate seasonal phenological development from BBCH scale recording - Christine Cornelius; Hannes Petermeier; Nicole Estrella; Annette Menzel (International Journal of Biometeorology, 2014)

Chilling outweighs photoperiod in preventing precocious spring development - Julia Laube; Tim H. Sparks; Nicole Estrella; Josef Höfler; Donna P. Ankerst; Annette Menzel (Global Change Biology, 2014)
It is well known that increased spring temperatures cause earlier onset dates of leaf unfolding and flowering. However, a temperature increase in winter may be associated with delayed development when species' chilling requirements are not fulfilled. Furthermore, photosensitivity is supposed to interfere with temperature triggers. To date, neither the relative importance nor possible interactions of these three factors have been elucidated. In this study, we present a multispecies climate chamber experiment to test the effects of chilling and photoperiod on the spring phenology of 36 woody species. Several hypotheses regarding their variation with species traits (successional strategy, floristic status, climate of their native range) were tested. Long photoperiods advanced budburst for one‐third of the studied species, but magnitudes of these effects were generally minor. In contrast to prior hypotheses, photosensitive responses were not restricted to climax or oceanic species. Increased chilling length advanced budburst for almost all species; its effect greatly exceeding that of photoperiod. Moreover, we suggest that photosensitivity and chilling effects have to be rigorously disentangled, as the response to photoperiod was restricted to individuals that had not been fully chilled. The results indicate that temperature requirements and successional strategy are linked, with climax species having higher chilling and forcing requirements than pioneer species. Temperature requirements of invasive species closely matched those of native species, suggesting that high phenological concordance is a prerequisite for successful establishment. Lack of chilling not only led to a considerable delay in budburst but also caused substantial changes in the chronological order of species' budburst. The results reveal that increased winter temperatures might impact forest ecosystems more than formerly assumed. Species with lower chilling requirements, such as pioneer or invasive species, might profit from warming winters, if late spring frost events would in parallel occur earlier.

Changes in the timing of hay cutting in Germany do not keep pace with climate warming - Anna Bock; Tim H. Sparks; Nicole Estrella; Annette Menzel (Global Change Biology, 2013)
A unique long‐term phenological data set of over 110 000 records of 1st cutting dates for haymaking across Germany, spanning the years 1951–2011 was examined. In addition, we analyzed a long‐term data set in the beginning of flowering of meadow foxtail ( Alopecurus pratensis ) covering the last 20 years. We tested whether hay‐cutting dates (based on a human decision when to cut) showed trends, temperature relationships and spatial distribution similar to the development of this grassland species, and if these trends could be related to climate change. The timing of 1st hay cut was strongly influenced ( P P −1 ; P AES , which encourage later cutting) were likely to be responsible for the regional differences, while the general increase in AES appears to have confounded the overall trend in hay cutting in the last 20 years. Trends over time and responses to temperature were small relative to those associated with the phenology of meadow foxtail. The advance in phenology of this species is greater than the advance in hay cutting, implying that hay cutting may not be keeping pace with a changing climate, which may have a positive effect on grassland ecology.

The impacts of climate change on the winter hardiness zones of woody plants in Europe - Philipp Gloning; Nicole Estrella; Annette Menzel (Theoretical and Applied Climatology, 2013)

Recent and future climate extremes arising from changes to the bivariate distribution of temperature and precipitation in Bavaria, Germany - Nicole Estrella; Annette Menzel (International Journal of Climatology, 2013)
This study assesses recent and future changes in joint temperature and precipitation regimes at 28 sites in Bavaria, based on statistical downscaling of the ECHAM4 B2 Scenario (WETTREG). Monthly meteorological data of three future decades (2021–2030, 2031–2040 and 2041–2050) were compared with modelled data for the reference period 1971–2000. The bivariate data were classified into four weather types or modes (cooler/drier, cooler/wetter, warmer/wetter and warmer/drier relative to the 1971–2000 reference period). For the three future decades, a systematic change at all locations throughout the year was revealed. Both the cooler modes are predicted to occur less frequently in future decades; changes in warmer modes differ seasonally: In winter months, they are predicted to occur in the warmer/wetter mode, whereas in spring and summer months in the warmer/drier mode. Climatological extremes were defined as monthly weather events outside the 90% confidence ellipse of a Gaussian model of events in the reference period. An increase of extremes in the decade 2041–2050 was striking for June, which is predicted to be warmer and drier for half of the years. The same decade is predicted to experience the most extreme warm and wet modes, one in three Februarys and one in two winters are likely to be in this mode. The magnitude of these future changes in climate was related to the present mean annual temperature of the stations by rank regression. Stations with currently cooler climates are more likely to retain the normal conditions of the baseline period in contrast to currently warmer stations where the increase of extreme warm and wet conditions in summer and winter is expected to be larger. Copyright © 2012 Royal Meteorological Society

Spatio-temporal investigation of flowering dates and pollen counts in the topographically complex Zugspitze area on the German–Austrian border - Susanne Jochner; Chiara Ziello; Andreas Böck; Nicole Estrella; Jeroen Buters; Ingrid Weichenmeier; Heidrun Behrendt; Annette Menzel (Aerobiologia, 2012)

Comprehensive methodological analysis of long‐term changes in phenological extremes in Germany - Christoph Schleip; Donna P. Ankerst; Andreas Böck; Nicole Estrella; Annette Menzel (Global Change Biology, 2012)
This study reports on alterations in the magnitude and frequency of extremes in reproductive phenology using long‐term records (1951–2008) for plant species widely distributed across Germany. For each of fourteen indicator phases studied, time series of annual onset dates at up to 119 stations, providing 50–58 years of observation, were standardized by their station mean and standard deviation. Four alternative statistical models were applied and compared to derive probabilities of extreme early or late onset times for the phases: (1) Gaussian models were used to describe decadal probabilities of standardized anomalies, defined by data either falling below the 5th or exceeding the 95th percentile. (2) Semi‐parametric quantile regression was employed for flexible and robust modelling of trends in different quantiles of onset dates. (3) Generalized extreme value distributions ( GEV ) were fitted to annual detrended minima and maxima of standardized anomalies, and (4) Generalized Pareto distributions ( GPD ) were fitted to extremes defined as peaks over threshold. Probabilities of extreme early phenological events inferred from Gaussian models, increased on average from 3 to 12%, whereas probabilities of extreme late phenological events decreased from 6 to 2% over the study period. Based on quantile regressions, summer and autumn phases revealed a more pronounced advancing pattern than spring phases. Estimated return levels by GEV were similar for the GPD methods, indicating that extreme early phenological events of magnitudes 2.5, 2.8, and 3.6 on the detrended standardized anomaly scale would occur every 20 years for spring, summer and autumn phases, respectively. This corresponds to absolute onset advances of up to 2 months depending on the season and species. This study demonstrates how extreme phenological events can be accurately modelled even in cases of inherently small numbers of observations, and underlines the need for additional evaluation related to their impacts on ecosystem functioning.

The influence of altitude and urbanisation on trends and mean dates in phenology (1980–2009) - Susanne C. Jochner; Tim H. Sparks; Nicole Estrella; Annette Menzel (International Journal of Biometeorology, 2012)

Effects of recent warm and cold spells on European plant phenology - Annette Menzel; Holm Seifert; Nicole Estrella (International Journal of Biometeorology, 2011)

A comparison of methods to estimate seasonal phenological development from BBCH scale recording - Christine Cornelius; Hannes Petermeier; Nicole Estrella; Annette Menzel (International Journal of Biometeorology, 2011)

Bayesian analysis of the species-specific lengthening of the growing season in two European countries and the influence of an insect pest - Annette Menzel; Nicole Estrella; Werner Heitland; Andreja Susnik; Christoph Schleip; Volker Dose (International Journal of Biometeorology, 2008)

Trends and temperature response in the phenology of crops in Germany - NICOLE ESTRELLA; TIM H. SPARKS; ANNETTE MENZEL (Global Change Biology, 2007)
The phenology of 78 agricultural and horticultural events from a national survey in Germany spanning the years 1951–2004 is examined. The majority of events are significantly earlier now than 53 years ago, with a mean advance of 1.1–1.3 days per decade. The mean trends for ‘true phases’, such as emergence and flowering, of annual and perennial crops are not significantly different, although more trends (78% vs. 46%) are significant for annual crops. We attempt to remove the influence of technological advance or altered farming practices on phenology by detrending the respective time series by linear regression of date (day number) on year. Subsequently, we estimate responses to mean monthly and seasonal temperature by correlation and regression in two ways; with and without removing the year trend first. Nearly all (97%) correlation coefficients are negative, suggesting earlier events in warmer years. Between 82% and 94% of the coefficients with seasonal spring and summer temperatures are significant. The conservative estimate (detrended) of mean temperature response against mean March–May temperature (−3.73 days °C −1 ) is significantly less than the full estimate (−4.31 days °C −1 ), the ‘true’ size of phenological temperature response may lie in between. Perennial crops exhibited a significantly higher temperature response to mean spring temperature than the annual crops.

European phenological response to climate change matches the warming pattern - ANNETTE MENZEL; TIM H. SPARKS; NICOLE ESTRELLA; ELISABETH KOCH; ANTO AASA; REIN AHAS; KERSTIN ALM‐KÜBLER; PETER BISSOLLI; OL'GA BRASLAVSKÁ; AGRITA BRIEDE; FRANK M. CHMIELEWSKI; ZALIKA CREPINSEK; et al. (Global Change Biology, 2006)
Global climate change impacts can already be tracked in many physical and biological systems; in particular, terrestrial ecosystems provide a consistent picture of observed changes. One of the preferred indicators is phenology, the science of natural recurring events, as their recorded dates provide a high‐temporal resolution of ongoing changes. Thus, numerous analyses have demonstrated an earlier onset of spring events for mid and higher latitudes and a lengthening of the growing season. However, published single‐site or single‐species studies are particularly open to suspicion of being biased towards predominantly reporting climate change‐induced impacts. No comprehensive study or meta‐analysis has so far examined the possible lack of evidence for changes or shifts at sites where no temperature change is observed. We used an enormous systematic phenological network data set of more than 125 000 observational series of 542 plant and 19 animal species in 21 European countries (1971–2000). Our results showed that 78% of all leafing, flowering and fruiting records advanced (30% significantly) and only 3% were significantly delayed, whereas the signal of leaf colouring/fall is ambiguous. We conclude that previously published results of phenological changes were not biased by reporting or publication predisposition: the average advance of spring/summer was 2.5 days decade −1 in Europe. Our analysis of 254 mean national time series undoubtedly demonstrates that species' phenology is responsive to temperature of the preceding months (mean advance of spring/summer by 2.5 days°C −1 , delay of leaf colouring and fall by 1.0 day°C −1 ). The pattern of observed change in spring efficiently matches measured national warming across 19 European countries (correlation coefficient r =−0.69, P

Integration of flowering dates in phenology and pollen counts in aerobiology: analysis of their spatial and temporal coherence in Germany (1992–1999) - Nicole Estrella; Annette Menzel; Ursula Krämer; Heidrun Behrendt (International Journal of Biometeorology, 2006)

Variations of the climatological growing season (1951–2000) in Germany compared with other countries - Annette Menzel; Gert Jakobi; Rein Ahas; Helfried Scheifinger; Nicole Estrella (International Journal of Climatology, 2003)
We analyse how variations in the climatological growing season, defined by single‐value thresholds of daily minimum and mean air temperature, mirror recent changes in plant phenological phases. In Germany (1951–2000, 41 climate stations), the dates of last spring frost T min A parallel evaluation of trends in the climatological growing season in other European countries (Austria, Switzerland, Estonia) supports this finding of a stronger lengthening of the frost‐free period than that of the growing season based on daily mean air temperature. The mean lengthening of the frost‐free period of 0.50 days per year in Austria and Switzerland (1951–99, 18 stations T mean ≥7 °C) in Austria and Switzerland (0.39 days per year) also approximates the respective result for Germany (0.36 days per year). However, in several cases, the trends increase with altitude (up to 500–900 m a.s.l.), but at high‐elevation climate stations (>950 m a.s.l.) weaker trends are again generally observed. Copyright © 2003 Royal Meteorological Society

Spatial and temporal variability of the phenological seasons in Germany from 1951 to 1996 - Annette Menzel; Nicole Estrella; Peter Fabian (Global Change Biology, 2001)
Various indications for shifts in plant and animal phenology resulting from climate change have been observed in Europe. This analysis of phenological seasons in Germany of more than four decades (1951–96) has several major advantages: (i) a wide and dense geographical coverage of data from the phenological network of the German Weather Service, (ii) the 16 phenophases analysed cover the whole annual cycle and, moreover, give a direct estimate of the length of the growing season for four deciduous tree species. After intensive data quality checks, two different methods – linear trend analyses and comparison of averages of subintervals – were applied in order to determine shifts in phenological seasons in the last 46 years. Results from both methods were similar and reveal a strong seasonal variation. There are clear advances in the key indicators of earliest and early spring (−0.18 to −0.23 d y −1 ) and notable advances in the succeeding spring phenophases such as leaf unfolding of deciduous trees (−0.16 to −0.08 d y −1 ). However, phenological changes are less strong during autumn (delayed by + 0.03 to + 0.10 d y −1 on average). In general, the growing season has been lengthened by up to −0.2 d y −1 (mean linear trends) and the mean 1974–96 growing season was up to 5 days longer than in the 1951–73 period. The spatial variability of trends was analysed by statistical means and shown in maps, but these did not reveal any substantial regional differences. Although there is a high spatial variability, trends of phenological phases at single locations are mirrored by subsequent phases, but they are not necessarily identical. Results for changes in the biosphere with such a high resolution with respect to time and space can rarely be obtained by other methods such as analyses of satellite data.

Spatial and temporal variability of the phenological seasons in Germany from 1951 to 1996 - Annette Menzel; Nicole Estrella; Peter Fabian (Global Change Biology, 2001)